#Sawfish: Social media to assess public perceptions, behaviors, and attitudes towards a critically endangered species - Saltzman, Julia; Graham, Jasmin; Wester, Julia; White, Easton R.; Macdonald, Catherine C. (Frontiers in Conservation Science, 2022)
Monitoring population size and dynamics is often both logistically difficult and costly for many species, especially those which are endangered or occur at relatively low densities. Recently, social media has emerged as a new tool for species monitoring. In this study, we expand on the use of social media posts as a tool to monitor the spatial and temporal distribution and public perceptions toward the smalltooth sawfish Pristis pectinata. We recorded 442 encounters with smalltooth sawfish from 2018 to 2021 in the form of Instagram posts. We identified locations of encounters within the following regions: Florida Keys, Everglades, South Florida (Miami/Fort Lauderdale), Caloosahatchee River, Bahamas, Upper Charlotte Harbor, Port St. Lucie, Ten Thousand Islands, Tampa, Naples, and Cape Canaveral. We found the greatest number of encounters occurred in the Florida Keys. In addition to spatiotemporal analysis, we used the captions of the posts to assess public attitudes and behaviors toward this charismatic species. This analysis revealed individuals who encounter sawfish feel in general positive about their experience (51.8% described their encounter using positive language). We also found that sawfish were frequently caught as bycatch when other species (e.g., shark, tarpon, bonefish) were being targeted. Notably, in 12.6% of cases where sawfish were caught, they were being directly targeted. We also identified specific illegal handling behaviors from image and caption analysis. In addition to caught sawfish, we found sawfish are frequently observed by beachgoers, boaters, and divers— however, in many cases these encounters may not be reported.